The dark side - O'Neill, Anthony, 1964- (Simon & Schuster Paperbacks, 2016)
"In this dark and gripping sci-fi noir, an exiled police detective arrives at a lunar penal colony just as a psychotic android begins a murderous odyssey across the far side of the moon." --